High Levels of Neutrophil Extracellular Traps Persist in the Lower Respiratory Tract of Critically Ill Patients With Coronavirus Disease 2019. (20th May 2021) - Ouwendijk, Werner J D; Raadsen, Matthijs P; van Kampen, Jeroen J A; Verdijk, Robert M; von der Thusen, Jan H; Guo, Lihui; Hoek, Rogier A S; van den Akker, Johannes P C; Endeman, Henrik; Langerak, Thomas; Molenkamp, Richard; Gommers, Diederik; et al.
Abstract: Lower respiratory tract (LRT) disease induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can deteriorate to acute respiratory distress syndrome (ARDS). Because the release of neutrophil extracellular traps (NETs) is implicated in ARDS pathogenesis, we investigated the presence of NETs and correlates of pathogenesis in blood and LRT samples of critically ill patients with COVID-19. Plasma NET levels peaked early after intensive care unit admission and were correlated with the SARS-CoV-2 RNA load in sputum and levels of neutrophil-recruiting chemokines and inflammatory markers in plasma samples. The baseline plasma NET quantity was correlated with disease severity but was not associated with soluble markers of thrombosis or with development of thrombosis. High NET levels were present in LRT samples and persisted during the course of COVID-19, consistent with the detection of NETs in bronchi and alveolar spaces in lung tissue from deceased patient with COVID-19. Thus, NETs are produced and retained in the LRT of critically ill patients with COVID-19 and could contribute to SARS-CoV-2–induced ARDS disease. Abstract : Aberrant neutrophil extracellular trap (NET) formation is implicated in acute respiratory distress syndrome (ARDS) pathogenesis. We demonstrate that NETs are present in blood and persist at high levels in the lower respiratory tract of critically ill patients with coronavirus disease 2019 and ARDS.